Robust adaptive fault tolerant control for a linear cascaded ODE-beam system - Liu, Zhijie; Liu, Jinkun; He, Wei (Automatica (Oxford), 2018)
In this paper, we present fault tolerant control design for a class of cascaded systems described by ordinary differential equations (ODEs) and an Euler–Bernoulli beam (EBB). The objective of this study is to design a robust adaptive fault tolerant control such that the global stability of the resulting closed-loop cascaded system is ensured and asymptotic tracking can be achieved subject to actuator failures, parameter uncertainty and external disturbances. The Lyapunov’s direct method is used to design the control schemes and prove the stability of the closed-loop system. Finally, the results are illustrated using numerical simulations for control performance verification.